Evaluation of tobacco specific nitrosamines exposure by quantification of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) in human hair of non-smokers - Pérez-Ortuño, Raúl (Sci Rep, 2016)
Chronic exposure to specific carcinogens present in secondhand smoke has been associated with different types of cancers. Hair is an ideal matrix to develop a proper biomarker as it absorbs substances in circulation and allows measuring their average concentration over long periods of time. A method was developed for the simultaneous quantification of nicotine, cotinine, NNN, NNK and NNAL in 20 mg human hair samples. Concentrations were significantly different depending on the declared exposure. This study shows for the first time that NNK is present in hair samples from non-smokers in concentrations much higher than any other tobacco specific nitrosamine. NNN could also be detected in samples from the most exposed non-smokers while, as previously reported, NNAL was undetectable. NNK correlates well with nicotine and cotinine (rsp = 0.774 and rsp = 0.792 respectively, p < 0.001 in both cases). However, NNN concentrations did not correlate with any of the other analytes. Ratios between NNK and nicotine show variability with different concentrations of NNK present in samples with similar nicotine values. NNK has proven to be the best marker of tobacco specific nitrosamines in hair. Monitoring NNK may provide a good estimation of cancer risk associated with exposure to secondhand smoke.